2018
DOI: 10.1371/journal.pone.0197506
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of differentially expressed genes involved in selenium accumulation in tea plant (Camellia sinensis)

Abstract: Tea plant (Camellia sinensis) has strong enrichment ability for selenium (Se). Selenite is the main form of Se absorbed and utilized by tea plant. However, the mechanism of selenite absorption and accumulation in tea plant is still unknown. In this study, RNA sequencing (RNA-seq) was used to perform transcriptomic analysis on the molecular mechanism of selenite absorption and accumulation in tea plant. 397.98 million high-quality reads were obtained and assembled into 168,212 unigenes, 89,605 of which were ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 65 publications
5
40
0
Order By: Relevance
“…The Camellia sinensis plant (the raw material of tea) can absorb Se from the soil, and Se then accumulates in the leaves . Previous studies have demonstrated that the presence of Se enhances the antioxidant, prebiotic, and anti‐carcinogenic activity of tea .…”
Section: Introductionmentioning
confidence: 99%
“…The Camellia sinensis plant (the raw material of tea) can absorb Se from the soil, and Se then accumulates in the leaves . Previous studies have demonstrated that the presence of Se enhances the antioxidant, prebiotic, and anti‐carcinogenic activity of tea .…”
Section: Introductionmentioning
confidence: 99%
“…As previous studies showed, the frequency of TTC repeat motif in Arabidopsis is higher in CDS than that in 5' UTR and intron. This may be as a result of codon usage bias [8]. However, compared to the genome background, there is no enrichment of this motif in the genic regions in RP genes, especially in the 5' UTR region, and only 10% RP genes has this motif in their 5' UTR regions and is significant lower than the genome background.…”
Section: O Sativa Rp Genes Have Special Sequence Features Compared Tmentioning
confidence: 90%
“…It also exhibits extremely strong positional bias in the [−200, 0] bp promoter regions of RP genes with a chi square value of 973.4. In addition to its general existence in RP genes, Motif3 is also found to be associated with dark-induced genes and over-represented in genes under circadian regulation in Arabidopsis [8]. Motif5 and motif6 are structurally related to motif2 and motif3 and can be considered as derivatives of these two motifs.…”
Section: Identification Of Putative Dna-binding Motifs In the 5' Flanmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 71 temperature stress-responsive proteins were identified through MALDI-TOF-TOF analysis[35]. Transcriptome sequencing has become a powerful technique for elucidating new genes and their related biochemical pathways in non-model plants because of its high throughput, low cost and large data output [36]. Metabolomics is a new field in the post-genome era that reveals the changing roles of metabolites in various tissues [37].…”
Section: Discussionmentioning
confidence: 99%